The new world : los cuerpos velados de Paco Lara-Barranco - Romero López, Sérgio (2019)
This paper aims to show how the veiling action of the medium over the representation of the body in the work of Paco Lara-Barranco operates as an incentive for the physical and affective mobilization of the concerned observer